Prosperity, great compression and Reaganomics: lessons for economic policy - Osiichuk, Dmytro (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
During the 20th century USA went through several radical swings of economic policy being the response to drastic societal, technological and ideological transformations. American economy endured several crises and experienced intensive sustained growth, which eventually transformed it into the world powerhouse. Basing on its historic record and with the benefit of hindsight, relevant lessons for economic policy can be derived. Three sub-periods of the American economic history, i.e. Prosperity (1920-1929), Great Compression (1937-1947), and Reaganomics (1981-1989), have been subject to positive analysis with the goal of suggesting answers to fundamental dilemmas of political economy. Particular attention is drawn towards evolution of institutional environment, income distribution policy and theoretical assumptions underlying policy making. We highlight the most prominent ideological pitfalls, which materialized in the American economic history, but which have not been properly addressed by the policymakers and engendered pathological processes in the political and social systems.

W XX wieku Stany Zjednoczone przeszły przez kilka radykalnych transformacji polityki gospodarczej będących odpowiedzią na zachodzące społeczne, technologiczne i ideologiczne zmiany. Amerykańska gospodarka przeżyła kilka kryzysów i doświadczyła intensywnego wzrostu, który uczynił ją światowym liderem. Bazując na tym historycznym doświadczeniu, możemy wyciągnąć ważne wnioski dla polityki gospodarczej. Trzy podokresy historii ekonomicznej Stanów Zjednoczonych – Prosperity (1920–1929), ‘wielka kompresja’ (1937–1947) oraz Reaganomika (1981–1989) – są poddane pozytywnej analizie w celu znalezienia odpowiedzi na fundamentalne dylematy polityki gospodarczej. Szczególną uwagę poświęcono zmianom instytucjonalnym, polityce redystrybucyjnej i teoretycznym założeniom kształtującym politykę ekonomiczną. Analizowane są ideologiczne złudzenia, które się zmaterializowały w amerykańskiej gospodarce i które nie zostały w odpowiedni sposób zaadresowane przez rządzących, powodując patologiczne zjawiska w polityce i społeczeństwie.
Keywords: economic policy; Prosperity; Great Compression; Reaganomics; polityka gospodarcza; Prosperity; wielka kompresja; Reaganomika